Cancer and Opium Addiction - Hossein Ghahremani; Alireza Mosavi Jarrahi; Siamak Salami (Asian Pacific Journal of Cancer Biology, 2019)
Drug abuse remains a serious health and social threat in the world. According to the United Nations Office of Drugs and Crime (UNODC) 1n 2010, an estimated 16.5 million people use opium or its derivatives illicitly (1). Meanwhile, Iran has the first rank in the prevalence of opium consumption (2), and Opium is the most commonly abused drug in Iran (8). Opium is the air-dried extract obtained from the seed capsules of the opium poppy, which is used for recreational or medical purposes in different parts of the world (3).  Approximately 8 to 14 percent of opium is made up of morphine, which is processed chemically to produce heroin and other synthetic opioids for medicinal use and also for drug abuse (4).